Metode Simple Additive Weighting Dalam Sistem Pendukung Keputusan Untuk Pemilihan Mobil LCGC - Hendry Hendry; Chairul Rizal; Supiyandi Supiyandi; Muhammad Noor Hasan Siregar (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Low Cost Green Car (LCGC) is a new breakthrough made by the government in the automotive world, especially in Indonesia. With the support of environmentally friendly concepts this type of LCGC car has become an alternative for consumers who want a car especially in Indonesia. To estimate LCGC cars according to needs, you can use a decision support system with a simple additive weighting (SAW) method. Data obtained from observations and interviews conducted through sales and car mechanics or experts who are more knowledgeable about market conditions and community needs. The results achieved are designing a decision support system application that predicts LCGC cars that fit consumers' desires based on price, engine capacity, safety features, fuel economy, cabin accommodation. By determining the preference value of each alternative, ranking is made so that from the alternatives there is the best alternative.